2023
DOI: 10.3390/su16010318
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility of Cultural Heritage Sites for People with Disabilities: A Case Study on Krakow Museums

Zygmunt Kruczek,
Katarzyna Gmyrek,
Danuta Ziżka
et al.

Abstract: The aim of this paper is to assess the accessibility of flagship cultural attractions—that is, museums located in Krakow, a city with a rich historical heritage included in the UNESCO World Cultural and Natural Heritage List and distinguished by being a recipient of the Access City Award—for people with disabilities. This research shows the degree to which these museums have been adapted to receive visitors with disabilities. Assessments were also conducted with regard to access to the museums’ websites and th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…This requires increasing their engagement levels in the public domain, and accessible tourism, including inclusive museums, is on the rise. A growing number of hotels, restaurants, museums, and attractions are announcing their accessibility to individuals with disabilities [33,34].…”
Section: Theme 1: Inclusive Design For Museum Presentationsmentioning
confidence: 99%
See 3 more Smart Citations
“…This requires increasing their engagement levels in the public domain, and accessible tourism, including inclusive museums, is on the rise. A growing number of hotels, restaurants, museums, and attractions are announcing their accessibility to individuals with disabilities [33,34].…”
Section: Theme 1: Inclusive Design For Museum Presentationsmentioning
confidence: 99%
“…Furthermore, according to Kruczek et al [33], the COVID-19 pandemic demonstrated the potential of mobile phone technologies to enhance the accessibility of tourist destinations, particularly museums, for individuals with sensory impairments. Technology has been used in various ways to enhance accessibility, including the provision of online communication tools, smartphones equipped with audio guides, and the capability to directly translate text into sign language [66,67].…”
Section: Mobile Device Technologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…A civilization is not detached from its historical past, which contains many valuable relics that identify the level of its development (Kruczek et al, 2024;Zenucchini et al, 2024). These relics include inscriptions (Rodway, 2020), ancient manuscripts (Suryana et al, 2024),, and other artefacts that should not be overlooked (Savino & Tonazzini, 2024;Utomo & Anindyarini, 2023).…”
Section: Theoretical Framework Ancient Manuscripts In Indonesiamentioning
confidence: 99%